Electrochemical Approach in Description of a Nerve Impulse - Berezin, Andrey; Shmid, Alexander (Edelweiss Applied Science and Technology, 2018)
Nerve impulse has been simulated as an ion–acoustic breather containing the internal FPU recurrence spectrum. The strong electrolyte of intracellular fluid is interpreted as dense plasma where electroacoustic solitons can propagate. The dynamics of sodium ion concentration is described by the sine-Gordon equation while the dynamics of proton concentration is done by the Korteweg de Vries equation. The system of these coupled equations has a breather solution having an intrinsic structure with the Fermi–Pasta–Ulam recurrence. Its spectrum possesses a dynamic memory for the initial conditions of its modes. Such breathers can be generated in firing process of a neuron. The information capacity of each breather can reach 1014 bits.